MYB76 Inhibits Seed Fatty Acid Accumulation in Arabidopsis - Duan, Shaowei; Jin, Changyu; Li, Dong; Gao, Chenhao; Qi, Shuanghui; Liu, Kaige; Hai, Jiangbo; Ma, Haoli; Chen, Mingxun (Frontiers in Plant Science, 2017)
The MYB family of transcription factors is important in regulatory networks controlling development, metabolism and responses to biotic and abiotic stresses in Arabidopsis. However, their role in regulating fatty acid accumulation in seeds is still largely unclear. Here, we found that MYB76, localized in the nucleus, was predominantly expressed in developing seeds during maturation. The myb76 mutation caused a significant increase in the amounts of total fatty acids and several major fatty acid compositions in mature seeds, suggesting that MYB76 functioned as an important repressor during seed oil biosynthesis. RNA sequencing and quantitative real-time PCR analysis revealed remarkable alteration of numerous genes involved in photosynthesis, fatty acid biosynthesis, modification, and degradation, and oil body formation in myb76 seeds at 12 days after pollination. These results help us to understand the novel function of MYB76 and provide new insights into the regulatory network of MYB transcriptional factors controlling seed oil accumulation in Arabidopsis.